Make Your Movie : What You Need to Know About the Business and Politics of Filmmaking. - Freedman Doyle, Barbara (Elsevier Science, 2012)
This book is for anyone interested in the business of breaking into the movies. Learn who the key players are when it comes to getting a movie made and how to navigate the politics of the€filmmaking from start to finish from first pitch to€filling€movie seats. €Understanding how a movie makes money and who actually makes it happen has never been easierReaders will benefit from guidance on finding a mentor and networking even when they don't know anyoneThe inside scoop has never been this accessible, from which film festivals really matter to how to start a production compan.